Pengelolaan Data Pemilih Pemilihan Gubernur Dan Wakil Gubernur Tahun 2020 Di Komisi Pemilihan Umum Kabupaten Minahasa Tenggara - Yuliana Christine Handayani; Daud M. Liando; Johny Peter Lengkong (Sam Ratulangi University, 2022)
This study aims to analyze voter data management in the 2020 Governor and Deputy Governor elections at the General Election Commission of Southeast Minahasa Regency. The research method used in this research is a descriptive qualitative method with a research focus focused on the dimensions of planning, organization and supervision of voter data management. Sources of research data consist of primary data and secondary data with data collection techniques using interview techniques, observation and documentation. The data obtained were analyzed by means of data reduction, data presentation and drawing conclusions. The results showed that the planning process in the form of updating voter data had been carried out based on GEC regulations. The GEC together with the ad hoc body that handles voter data, both at the village and sub-district levels, manages the data obtained by juxtaposing the dukcapil data, which in fact contains voter data that does not match, starting from gender errors, even the voter's domicile. In the supervision process, the GEC is running well, which can be seen from the discovery of duplicate data that does not match the identity card and dukcapil data, so improvements are made. The management of voter data for the 2020 Governor and Deputy Governor elections has been carried out well even though there were problems that arose both before and after the election.